Physical properties of sago fine waste as a fine aggregate in material of construction - Abd Wahab, Norhayati; Adnan, Suraya Hani; Ibrahi, Abdul Hadi Izaan (Penerbit UTHM, 2022)
Sarawak is one of the many that have sago and commercialized crops. The total area of sago cultivation in Sarawak is 51,518 hectares. In process of sago starch, every day contributed about 60 tons of sago waste is dumped into the nearest river. Sand, on the other hand, is typically gathered by employing machinery along the riverbank, which considerably contributes to the river's environment being harmed and contributing to global warming. Extensive research on waste materials has been performed for environmental protection and sustainable development. Sago waste, also known as Sago Fine Waste (SFW), will be handled; it has been utilized as a substitute for fine aggregations (sand). It may be inferred that, in addition to protecting the environment and contributing to sustainable development, this study can be investigated further as a novel construction material. To make SFW as a substitute for sand, physical properties are determined such particle size distribution, particle density and water absorption test (PDWA) and bulk density test. Fineness modulus of SFW is 2.98, specific gravity 0.45, water absorption 45% and bulk density is1270 kg/m3 . From the result, SFW is potentially SFW is potentially replacement for fine aggregate in construction material.